Availability, Accessibility, and Coverage of Needle and Syringe Programs in Prisons in the European Union. Issue 1 (11th September 2020) - Moazen, Babak; Dolan, Kate; Saeedi Moghaddam, Sahar; Lotfizadeh, Masoud; Duke, Karen; Neuhann, Florian; Stöver, Heino; Jahn, Albrecht
Abstract: Needle and syringe programs (NSPs) are among the most effective interventions for controlling the transmission of infection among people who inject drugs in prisons. We evaluated the availability, accessibility, and coverage of NSPs in prisons in European Union (EU) countries. In line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria, we systematically searched 4 databases of peer-reviewed publications (MEDLINE (PubMed), ISI Web of Science, EBSCO, and ScienceDirect) and 53 databases containing gray literature to collect data published from January 2008 to August 2018. A total of 23, 969 documents (17, 297 papers and 6, 672 gray documents) were identified, of which 26 were included in the study. In 2018, imprisonment rates in 28 EU countries ranged between 51 per 100, 000 population in Finland and 235 per 100, 000 population in Lithuania. Only 4 countries were found to have NSPs in prisons: Germany (in 1 prison), Luxembourg (no coverage data were found), Romania (available in more than 50% of prisons), and Spain (in all prisons). Portugal stopped an NSP after a 6-month pilot phase. Despite the protective impact of prison-based NSPs on infection transmission, only 4 EU countries distribute sterile syringes among people who inject drugs in prisons, and coverage of the programs within these countries is very low. Since most prisoners will eventually return to the community, lack of NSPs in EU prisons not only is a threat to the health of prisoners but also endangers public health.